1993
DOI: 10.1159/000187558
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Renin-Angiotensin System Stimulation on Erythropoietin Production in Patients with Various Forms of Arterial Hypertension

Abstract: Recent studies suggest the existence of a relationship between the renin-angiotensin system and erythropoietin (EPO) secretion. It has been studied whether patients with various forms of arterial hypertension (essential, renal, renovascular, in the course of arteritis) differ with respect to EPO secretion and whether EPO serum levels are related to renin response induced by dietary sodium restriction to 10-20 mmol Na/24 h for 3 days and upright body position for 3 h. Patients with different forms of hypertensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…This indirectly shows that there were no differences in the salt-sensitivity of patients between the studied groups, an finding important with respect to the study of Naomi et al (37) who found that sodium-sensitivity index may determine EPO response to changes in dietary sodium intake. It is noteworthy that we found a slight decline in EPO levels in response to sodium restriction in all groups, a finding which we reported not only in essential but also in some secondary forms of hypertension (27). These results are, however, difficult to explain because in agreement with the hypothesis of Kurtz and Eckardt (38) we should expect that the decrease in the fractional sodium excretion indicating increased tubular reabsorption of sodium, i. e., "metabolic strain" for proximal tubules, should result in the stimulation of EPO production.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This indirectly shows that there were no differences in the salt-sensitivity of patients between the studied groups, an finding important with respect to the study of Naomi et al (37) who found that sodium-sensitivity index may determine EPO response to changes in dietary sodium intake. It is noteworthy that we found a slight decline in EPO levels in response to sodium restriction in all groups, a finding which we reported not only in essential but also in some secondary forms of hypertension (27). These results are, however, difficult to explain because in agreement with the hypothesis of Kurtz and Eckardt (38) we should expect that the decrease in the fractional sodium excretion indicating increased tubular reabsorption of sodium, i. e., "metabolic strain" for proximal tubules, should result in the stimulation of EPO production.…”
Section: Discussionsupporting
confidence: 79%
“…Despite these findings little interest has been focused so far on the contribution of endogenous erythropoietin to the pathogenesis of essential hypertension (26,27). Taking the aforementioned findings into account, in the present study we tried to test the hypothesis that endogenous erythropoietin is involved in the pathogenesis of obesity-related hypertension.…”
mentioning
confidence: 96%
“…In patients with hypertension and normal renal excretory function, a direct correlation between plasma renin activity and serum Epo was seen in patients with glomerulonephritis or pyelonephritis. 18 Previous work from this laboratory documents anaemia due to Epo deficiency in patients with Type 1 diabetes 10 with hyporeninaemic hypoaldosteronism. Plasma renin activity is significantly lower in haemodialysis patients requiring exogenous Epo to maintain a haematocrit of approximately 30%, compared with similar patients who do not require Epo.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin and plasma aldosterone were measured with radioimmunoassay as previously described [13]and all other parameters with standard laboratory methods.…”
Section: Methodsmentioning
confidence: 99%